The quality of migrant patients' primary healthcare experiences and patient-centered medical home achievement by community health centers: results from the China greater bay area study - Yongjun Huo; Xun Kang; Chenyang Zhong; Leiyu Shi; Ruqing Liu; Ruwei Hu (BMC, 2023)
Abstract Background In China, Community Health Centers (CHCs) provide primary healthcare (PHC); however, few studies have examined the quality of PHC services experienced by migrant patients. We examined the potential association between the quality of migrant patients' PHC experiences and the achievement of Patient-Centered Medical Home by CHCs in China. Methods Between August 2019 and September 2021, 482 migrant patients were recruited from ten CHCs in China's Greater Bay Area. We evaluated CHC service quality using the National Committee for Quality Assurance Patient-Centered Medical Home (NCQA-PCMH) questionnaire. We additionally assessed the quality of migrant patients' PHC experiences using the Primary Care Assessment Tools (PCAT). General linear models (GLM) were used to examine the association between the quality of migrant patients' PHC experiences and the achievement of PCMH by CHCs, adjusting for covariates. Results The recruited CHCs performed poorly on PCMH1, Patient-Centered Access (7.2 ± 2.0), and PCMH2, Team-Based Care (7.4 ± 2.5). Similarly, migrant patients assigned low scores to PCAT dimension C-First-contact care-which assesses access (2.98 ± 0.03), and D-Ongoing care (2.89 ± 0.03). On the other hand, higher-quality CHCs were significantly associated with higher total and dimensional PCAT scores, except for dimensions B and J. For example, the total PCAT score increased by 0.11 (95% CI: 0.07-0.16) with each increase of CHC PCMH level. We additionally identified associations between older migrant patients (> 60 years) and total PCAT and dimension scores, except for dimension E. For instance, the average PCAT score for dimension C among older migrant patients increased by 0.42 (95% CI: 0.27-0.57) with each increase of CHC PCMH level. Among younger migrant patients, this dimension only increased by 0.09 (95% CI: 0.03-0.16). Conclusion Migrant patients treated at higher-quality CHCs reported better PHC experiences. All observed associations were stronger for older migrants. Our results may inform future healthcare quality improvement studies that focus on the PHC service needs of migrant patients.